The Development of the Usage of Blockchain for Waqf and Zakat Globally: A Bibliometric Study - Budi Santoso, Tulus; Kusuma, Akhmad (International Journal of Mechanical Computational and Manufacturing Research, 2023)
Zakat and waqf funds in the global scope are equivalent to 1% of the total GDP in the world. However, the usage of zakat and waqf funds is still not optimal. Blockchain could be used to supervise the management of the waqf and zakat. This study has a purpose for the topic development of previous studies related to the usage of blockchain for zakat and waqf management globally. This study used the bibliometric method to gather and analyze the secondary data. The data were collected from the Web of Science (SCI) website from 1979-2023. There were 415 metadata documents found and would be analyzed using R Studio software. The result showed that the majority of the total documents as in previous studies were article type. The co-authorship per paper was 23.13% from 415 documents. The affiliation countries of the authors with the biggest papers were Indonesia and Malaysia. They were also the two words that were most frequently used both in the abstract and in the title of the previous studies.